An introduction to German concrete poetry - Michaud, Joseph A. (Kansas State University, 1969)
Concrete poetry is a new and revolutionary poetry. It was developed less than two decades ago concurrently in Europe and South America by Eugen Gomringer, a German Swiss and the Noigandres group of Brazilian poets (Decio Pignatari, Augusto de Campos, Haroldo de Campos). In only 15 years it has grown to be an international movement. The first concrete poems were the result of years of experimentation. Gradually, a poetry developed which had a high visual impact due to a distillation of language. This was a poetry which concerned itself with the word rather than words, words, words or expressionistic squiggles". The word rather than the line became the basic linguistic unit. The emotion-charged, verbose streams of representational poetry were reduced to clear, light, rational structures in which the content was the very form itself. This reduction of language served to express a given content more concretely and to achieve “greater flexibility and freedom of Communication.”